Evaluation of the Ability of CMIP6 Global Climate Models to Simulate Precipitation in the Yellow River Basin, China - Wang, Lin; Zhang, Jianyun; Shu, Zhangkang; Wang, Yan; Bao, Zhenxin; Liu, Cuishan; Zhou, Xiong; Wang, Guoqing (Frontiers in Earth Science, 2021)
Choosing an appropriate GCM (Global Climate Model, GCM) is of great significance for the simulation of the hydrological cycle over a basin under future climate scenarios. In this study, the Rank Score Method (RS) with eight indicators were applied to comprehensively evaluate the suitability of 19 GCMs issued in the Sixth Global Atmosphere and Coupled Model Intercomparison Project (CMIP6) to the Yellow River Basin (YRB). The results indicated that: 1) The GCMs perform differently in simulating precipitation over the YRB with the top six GCMs ranking from MRI-ESM2-0, ACCESS-CM2, CNRM-CM6-1, CNRM-ESM2-1, FGOALS-f3-L, to MPI-ESM1-2-HR. 2) Most GCMs overestimated the precipitation, and poorly simulated the phase distribution of extremes mainly due to overstimulation of wet season span and precipitation amount in the season, although all GCMs could capture decadal feature of annual precipitation. Meanwhile, it is also found that most GCMs underestimated summer precipitation and overestimated spring precipitation. 3) The GCMs well simulated the spatial distribution of annual precipitation, with an overestimation in the source area, and an underestimation in the northern part of the middle reaches of YRB.